(untitled) (Research, Society and Development, 2020)
The analysis of the seed vigor has stood out for allowing greater precision, standardization, objectivity and speed in the evaluation of the physiological potential of seeds. The variation of the irrigation depth in the plant, can lead to expressive results in obtaining superior product. The final population of this crop in the field is directly proportional to the seed germination rate. In this sense, the objective of this work was to evaluate the quality of Santa Cruz and Speedy okra seeds produced under different irrigation depths. The design was randomized blocks with a 5 x 2 factorial (five irrigation depths: 25, 50, 75, 100 and 125% of ETc and two okra cultivars: Santa Cruz and Speedy) and four replications. At 70 days after anthesis, the fruits were harvested and the seeds were extracted and the moisture degree, varietal purity, thousand seed mass, accelerated aging test, germination pattern and electrical conductivity of seeds were tested. With the increase in irrigation depths, there was less seed germination for the two okra cultivars. The 100 and 125 ETc irrigation depths provided less electrical conductivity of the seeds for the two okra cultivars. Larger blades indicate greater rigidity of the seed coat. The okra cultivar Speedy responded with an increase in the Degree of moisture of the seeds and in the Mass of a thousand seeds up to the blade of 75% of the ETc.